PENGARUH PENAMBAHAN ANGKAK DAN KOMBINASI FILLER TEPUNG TERIGU DAN TEPUNG KETELA RAMBAT TERHADAP KUALITAS SOSIS SAPI - , dyah wahyuni ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was conducted to study the effects of anka rice as a natural dye with filler and its combination effect on physical quality, chemical, microstructure and sensory in beef sausage. Anka rice was used as powder were 0%, 0,1%, 0,2% and 0,3%. The filler were wheat flour and sweet potato flour with combination 20:0%, 15:5%, 10:10%, 5:15% and 0:20%. Each treatment consisted of three replications. The observed variables were chemical qualities (moisture, protein and fat), physical qualities (pH, water-holding capacity, and tenderness), microstructure and sensory (colour, taste, texture, aroma, and acceptability). The sausage data of chemical and physical quality were statistically analyzed using variance analysis of completely randomized design with factorial pattern (4 anka rice level x 5 filler combinations), followed by Duncanâs Multiple Range Test. Sausages microstructure were analyzed descriptively. Sensory quality was observed by panelists. Sensory quality was analysed by using Kruskal-Wallis Hedonic test, followed by quantitative descriptive analysis (QDA) in a model of spider web. The results indicated that the addition of anka rice as much as 0.3% showed the best results based on sensory quality (p<0,05), but did not change the chemical, physical, and microstructure quality. The addition of filler combination as much as 10:10% did not significantly affect the physical, microstructure, sensory and chemical quality in general because only the protein content significantly (p<0,05) changed. The addition of filler combination of wheat flour and sweet potato flour significantly decreased the protein content of sausage. There was no interaction between the addition of anka rice with filler combination of wheat flour and sweet potatoe flour.